ANALYSIS OF DIGITAL LITERACY PROGRAMS TO IMPROVE ELEMENTARY SCHOOL STUDENTS' 4C SKILLS - Irma Fateh Katun Kasanah; Yuli Prihatni; Suyono (SOSIOEDUKASI, 2026)
The industrial revolution 4.0 is driving faster changes towards education by implementing digital literacy that can create students with 4C skills. This study was conducted to answer the research question regarding the analysis of digital literacy programs to improve the 4C skills of elementary school students. This research is a qualitative descriptive study. This research was conducted at Tegalgondo 1 Public Elementary School. The sampling technique in this study used purposive sampling. The subjects of this study consisted of 10 teachers. The data collection technique in this study used a questionnaire. The research implementation time was from early November to the end of December 2025. The data analysis technique started from data collection, data reduction, data presentation, and conclusions. The results of the study showed that the average percentage of critical thinking skills was 82.70%, creative thinking skills with a percentage of 81.22%, communication skills with a percentage of 80.35%, and collaboration skills with a percentage of 80%. All four aspects of 4C skills are included in the high category, so it is concluded that the digital literacy program can improve 4C skills (critical thinking, creative thinking, collaboration, and communication skills).